2009
DOI: 10.1128/iai.00617-09
|View full text |Cite
|
Sign up to set email alerts
|

Association of Malaria-Induced Murine Pregnancy Failure with Robust Peripheral and Placental Cytokine Responses

Abstract: Malarial infection in nonimmune pregnant women is a major risk factor for pregnancy failure. The biological mechanisms that underlie malaria-associated fetal loss, however, are poorly understood. Plasmodium chabaudi AS infection during early pregnancy results in midgestational embryonic loss in naive C57BL/6 mice. To define the immunopathogenesis of this malaria-induced pregnancy compromise, cytokine production in plasma, spleen, and placenta cell culture supernatants during the first 11 days of infection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 44 publications
5
37
1
1
Order By: Relevance
“…However, our results indicated that the production of these cytokines in WT infected mice was clearly associated with the observed placental impairment (i.e., inflammation, tissue disorganization, and reduction of vascular space). A possible explanation for the absence of abortions in this study may be the time of infection, which, in contrast to previous studies (47), was chosen to allow the pregnancies to reach term in our murine model (3). In addition to the systemic maternal levels of TNF-␣, the placentas from the infected WT mice showed increased expression of TNF-␣ mRNA.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…However, our results indicated that the production of these cytokines in WT infected mice was clearly associated with the observed placental impairment (i.e., inflammation, tissue disorganization, and reduction of vascular space). A possible explanation for the absence of abortions in this study may be the time of infection, which, in contrast to previous studies (47), was chosen to allow the pregnancies to reach term in our murine model (3). In addition to the systemic maternal levels of TNF-␣, the placentas from the infected WT mice showed increased expression of TNF-␣ mRNA.…”
Section: Discussioncontrasting
confidence: 40%
“…In addition to TNF-␣, other proinflammatory cytokines, such as IFN-␥, have been implicated in spontaneous abortion in humans (46). Similarly, murine models developed in an attempt to induce pregnancy failure through malaria infection point to systemic increases in TNF-␣ and IFN-␥ production as a cause of abortions (47,48). In our model system, we did not observe an increase in abortion or reabsorption due to systemic TNF-␣ or IFN-␥ production.…”
Section: Discussionmentioning
confidence: 61%
“…Advances in understanding of malarial pathogenesis in humans during the early, highly vulnerable phases of pregnancy are few because the affected placenta is unavailable for study. P. chabaudi AS infection in murine pregnancy, which can be easily employed to investigate infection throughout the course of pregnancy [23, 25-27], is therefore highly valuable in identifying the molecular mechanisms underlying the pathogenesis of PM early in gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, trophoblast phagocytosis of red blood cells is associated with pregnancy loss in mice infected with P. chabaudi AS [23] as well as P. berghei [24]. Like P. berghei ANKA, P. chabaudi AS -iRBCs have also been reported to accumulate in placental tissue [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation